Evaluation of an Innovative Late‐Life Depression Training Program. Issue 1 (4th April 2013) - Smith, Marianne; Stolder, Mary Ellen; Liu, Megan Fang
<x xml:space="preserve">Abstract</x> Purpose This paper describes evaluation findings associated with an innovative, CD‐based, self‐directed training program that was designed to improve general practice nurses' abilities to identify and care for older adults with depression. Design and Methods A voluntary sample of nurses completed an evaluation that focused on participants' perceptions of changes in their knowledge and skills and usefulness of the program. Findings Quantitative items received high ratings, and narrative responses to open‐ended questions were largely positive. Practice Implications Many opportunities exist for psychiatric nurses to facilitate, support, and extend training principles to promote late‐life depression recognition and treatment.